1972
DOI: 10.1002/j.1537-2197.1972.tb10079.x
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Cell Cycles in Cultured Roots of Convolvulus

Abstract: The durations of the cell cycle in physiologically different regions of the meristem of cultured roots of Convolvulus arvensis were determined by the metaphase-accumulation technique involving colchicine. The cell cycle in the root cap increases from 13 hr in the actively dividing initials of the first tier to 155 hr in the slowly dividing initials of tiers 2-4 to an indeterminate value for derivatives of the initials in the root cap columella. The cycle times for the cells of the central cylinder and cortex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1973
1973
1976
1976

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Hitherto works showed that cytokinin activity increases in the roots of diseased plants by the direct or indirect influence of parasites (MATSBURA and NAKAHIRA 1968, PHILLIPS and TORREY 1972, VIZ.4ROVA 1973b, 1974c. When the roots were directly invaded by the parasite, striking structural changes were observed in the cortical cells together with an increased mitotic activity and with frequently occurring polyploid mitoses (MATTHYSSE and TORREY 1969).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hitherto works showed that cytokinin activity increases in the roots of diseased plants by the direct or indirect influence of parasites (MATSBURA and NAKAHIRA 1968, PHILLIPS and TORREY 1972, VIZ.4ROVA 1973b, 1974c. When the roots were directly invaded by the parasite, striking structural changes were observed in the cortical cells together with an increased mitotic activity and with frequently occurring polyploid mitoses (MATTHYSSE and TORREY 1969).…”
Section: Discussionmentioning
confidence: 99%
“…As roots show high concentrations of the cytokinins (KENDE 1965, VAADIA andITA! 1969) produced by their apical meristem (WEISS andVAADIA 1965, PHILLIPS andTORREY 1972), it must be taken into account that their influence manifests itself at the nearest neighborhood of their biosynthese, i. e. at the central cylinder, if their level increases in the roots of the diseased barley plants. Their influence upon the cortical cells is a secondary one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these changes, and the changes in ^', may be related to the formation of a quiescent centre in these roots (MacLeod and McLachlan, 1974). The quiescent centre may be the site of synthesis of growth hormones in the root (Phillips and Torrey, 1972) and such factors are know^n to influence cell proliferation (Van't Hof, 1968;Davidson and Webster, 1968;MacLeod, 1969;Webster and Davidson, 1969;Nagl, 1972a) and the response of root meristems to treatment with colchicine MacLeod, 1973a). On the other hand, the quiescent centre, which gradually increases in size during root development (Byrne and Heimsch, 1970;MacLeod and McLachlan, 1974), may form in response to the accumulation of growth factors in the root tip in the course of development.…”
Section: Treated Rootsmentioning
confidence: 99%
“…The growth of lateral root primordia is characterized by changes in both the parameters of cell proliferation (MacLeod and Davidson, 1968a;MacLeod, 1972a) and their response to treatment with colchicine (Davidson, 1965(Davidson, , 1969MacLeod, 1973a) and indol-3yl-acetic acid (IAA) (MacLeod, 1973a). Similarly, root apical meristems are structurally heterogeneous with respect to the duration of the mitotic cycle (Thompson and Clowes, 1968;Barlow, 1971;Phillips and Torrey, 1972) and the distribution of proliferating and quiescent cells (Clowes, 1971), and the various parts of these meristems exhibit different responses to, for example, colchicine (Davidson, 1961) or radiation (Clowes, 1963).…”
Section: Introductionmentioning
confidence: 99%